2013
DOI: 10.1148/radiol.12120255
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Dynamic Contrast-enhanced MR Imaging. Part II. Comparison of Intra- and Interobserver Variability with Manual Region of Interest Placement versus Semiautomatic Lesion Segmentation and Histogram Analysis

Abstract: A semiautomatic lesion segmentation and histogram analysis approach can provide a significant reduction in interobserver variability for DCE MR imaging measurements of K(trans) when compared with manual ROI methods, whereas intraobserver reproducibility is improved to some extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
90
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(97 citation statements)
references
References 28 publications
6
90
1
Order By: Relevance
“…To the best of our knowledge, the diagnostic accuracy of the nCBV obtained from the random manual ROIs placement and the semiautomatic segmentation method in brain tumor differential diagnosis has not been compared yet. Prior research assessed the manual and semiautomatic approach in the mass evaluation of various organs, but most of them focused on the reproducibility issue (22,23,32). The semiautomatic lesion segmentation significantly improves both intraobserver and interobserver reproducibility in the GBM nCBV measurement (22) and reduces interobserver variability in the permeability parameter (Ktrans) measurement from dynamic contrast enhancement MRI in uterine fibroid (23).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To the best of our knowledge, the diagnostic accuracy of the nCBV obtained from the random manual ROIs placement and the semiautomatic segmentation method in brain tumor differential diagnosis has not been compared yet. Prior research assessed the manual and semiautomatic approach in the mass evaluation of various organs, but most of them focused on the reproducibility issue (22,23,32). The semiautomatic lesion segmentation significantly improves both intraobserver and interobserver reproducibility in the GBM nCBV measurement (22) and reduces interobserver variability in the permeability parameter (Ktrans) measurement from dynamic contrast enhancement MRI in uterine fibroid (23).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research assessed the manual and semiautomatic approach in the mass evaluation of various organs, but most of them focused on the reproducibility issue (22,23,32). The semiautomatic lesion segmentation significantly improves both intraobserver and interobserver reproducibility in the GBM nCBV measurement (22) and reduces interobserver variability in the permeability parameter (Ktrans) measurement from dynamic contrast enhancement MRI in uterine fibroid (23). Bauknecht et al (32) showed improved reproducibility in the semiautomatic volume measurement of brain metastasis compared to the conventional linear method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations